Relationship Between Peer Pressure and Self Esteem in Adolescents - Astri Tanjung Mutia; Indah Sukmawati (Jurnal Neo Konseling, 2019)
When entering adolescence, adolescents are expected to be able to know their own worth and their worth towards others. This means that adolescents should be able to assess themselves positively by the extent to which adolescents are able to show that they are capable, meaningful, successful and valuable. The reality that occurs in the field are still many teenagers who are found there are teenagers who do not believe in their own abilities, do not dare to appear in front of the class, feel afraid and anxious when faced with a challenge, become victims of bullying, and are isolated from peer groups, etc. This study aims to describe peer pressure and adolescent self-esteem and to examine the relationship between peer pressure and adolescent self-esteem in Adabiah Padang High School. This type of research used in this research is descriptive quantitative correlational. The sample in this study amounted to 219 students. The results of the study revealed that: (1) peer pressure experienced by Adabiah Padang high school students was in the high category, (2) self-esteem possessed by Adabiah Padang high school students was in the low category, (3) there is a significant negative relationship between peer pressure and adolescent self-esteem at Adabiah Padang High School.